A comprehensive state‐of‐the‐art review on reliability assessment and charging methodologies of grid‐integrated electric vehicles. Issue 1 (22nd March 2023) - Singh, Saumya; Saket, Ram K.; Khan, Baseem
Abstract: This article presents a comprehensive review on the reliability assessment and charging methodologies of electric vehicles (EVs) connected to the grid. In the transportation industry, EVs are acknowledged as effective ideas for reducing the consumption of fossil fuels and the emission of greenhouse gases. The article presents a critical survey of the various types of EVs and their performance, generally depend on the proper interface between power electronics converters and energy storage devices. Bi‐directional converters are utilised to enhance efficiency and prolong battery life. This article explores an in‐depth analysis of the grid connected converter topologies for distribution networks, charging infrastructures and standards, battery charging technologies (merits/demerits), and most advanced off‐board and on‐board EV chargers. Evaluating the reliability of grid‐integrated EVs system is thus an important area of research. Then, the current research approaches vehicle‐to‐grid (V2G) and grid‐to‐vehicle (G2V) are demonstrated to describe travel behaviour, reliability parameters, and battery capacity associated with reliability and to assess the stability of the distribution system by incorporating EV discharging thresholds of both distribution networks and EVs. Finally, this article illustrates the positive as well as negative impacts of grid integration, issues related to EV converters, and specific suggestions for developing EV charging stations (CS) in the future. Abstract : This paper presents a comprehensive review on the reliability assessment and charging methodologies of electric vehicles (EVs) connected to the grid. In the transportation industry, EVs are acknowledged as effective ideas for reducing the consumption of fossil fuels and the emission of greenhouse gases.